Application of technology in operational management - Imam Wibowo (Sean Institute, 2024)
With the rapid development of information and communications technology, modern organizations are faced with opportunities to improve their operational efficiency and effectiveness through technology integration. This research aims to investigate and analyze the impact of implementing the latest technology in the context of operational management of an organization. This research uses a qualitative approach with descriptive methods. The research results show that the application of technology in operational management has a positive impact on the efficiency, productivity and quality of an organization's production results. The use of software systems such as Enterprise Resource Planning (ERP) and Supply-Chain Management (SCM) can improve interdepartmental integration, minimize data errors, and speed up workflow. Computerized Numerically Controlled (CNC) machines provide high precision in the production process. However, research also highlights challenges related to initial investment costs, maintenance costs, and risks of implementation errors that need to be carefully considered before adopting this technology. In conclusion, technology plays a crucial role in improving organizational operations, but wise implementation policies are required to maximize its benefits.